Muscular coordination of biceps brachii and brachioradialis in elbow flexion with respect to hand position - Kleiber, Tim; Kunz, Leo; Disselhorst-Klug, Catherine (Frontiers in Physiology, 2015)
Contribution of synergistic muscles towards specific movements over multi joint systems may change with varying position of distal or proximal joints. Purpose of this study is to reveal the relationship of muscular coordination of brachioradialis and biceps brachii during elbow flexion with respect to hand position and biomechanical advantages and disadvantages of biceps brachii. A group of 16 healthy subjects has been advised to perform 20 repetitions of single elbow flexion movements in different hand positions (pronated, neutral and supinated). With a speed of 20°/s, simultaneously sEMG of biceps brachii and brachioradialis and kinematics of the movement were recorded in a motion analysis laboratory. Normalized to MVC the sEMG amplitudes of both muscles contributing to elbow flexion movements were compared in pronated, supinated and neutral hand position over elbow joint angle. Significant differences in the contribution of brachioradialis were found in pronated hand position compared to supinated and neutral hand position while the muscular activity of biceps brachii shows no significant changes in any hand position. In conclusion, a statistical significant dependency of the inter-muscular coordination between biceps brachii and brachioradialis during elbow flexion with respect to hand position has been observed depending on a biomechanical disadvantage of biceps brachii.